PEMBERIAN PROBPEMBERIAN PROBIOTIK PADA MEDIA PEMELIHARAAN BENIH IKAN PATIN (Pangasius hypophthalmus) DALAM AKUARIUMIOTIK PADA MEDIA PEMELIHARAAN BENIH IKAN PATIN (Pangasius hypophthalmus) DALAM AKUARIUM - Khusnul Khotimah; Elva Dwi Harmilia; ramila sari (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT The purpose of this study was to determine the growth and viability of the seeds fish of patin by probiotics in maintenance media. This study will be conducted at the Laboratory Wet Water Cultivation Faculty of Agriculture, University of Muhammadiyah Palembang. This research was conducted using completely randomized design (CRD) non factorial with four levels of treatment factors and three replications. The level of treatment given factor is P0 = Probiotics 0 ml/L, P1 = probiotics 1.5 ml/L, P2 = probiotics 3.0 ml/L, and P3 = probiotics 4.5 ml/L. The parameters observed both its length and weight growth and survival. The result showed that the growth of the seed weight and length best patin obtained on addition of probiotic treatment of 1.5 ml / L is a weight of 10.71 grams and a length of 5.06 cm. whereas the survival is highest in the addition of probiotic treatment of 1.5 ml / L reached 93.33%. Key words: Probiotics, Seeds fish of Patin, Maintenance Media.